Validasi Komik Asertif Organ Reproduksi Seri "Bagian Tubuh" - Tri Suyati; Padmi Dhyah Yulianti; Ellya Rakhmawati (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2020)
Abstract: Sexual violence in early childhood is prevalent and shows an increasing prevalence. The impact caused by the occurrence of sexual violence experienced will affect the mental health of the victim. Therefore, early childhood needs to be saved from incidents of sexual violence because children are the future owners of the nation. Thus, the importance of equipping children with knowledge, attitudes and skills about themselves and their bodies to prevent sexual violence. The researchers in this study aim to produce Reproductive Organ Assertive Comics for early childhood and test the validity of assertive comics with the theme "Body Parts" as an effort to prevent sexual violence in young children. This research uses the design of Research and Development (R&D). There are ten stages carried out in this study. In this paper the researcher discusses only the content validity test of three expert judgments. Based on the results of the assessment of expert judgment, it was found that the comic assertive of reproductive organs (the prevention of sexual violence) with the theme "Parts of the Body" was appropriate to be used as an effort to prevent sexual violence for young children.